2020
DOI: 10.1155/2020/9046781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microvascular Structure Changes after Conbercept Treatment on Macular Edema Secondary to Retinal Vein Occlusion

Abstract: Aims. To confirm the therapeutic efficacy of conbercept for the treatment of macular edema (ME) secondary to retinal vein occlusion (RVO) by using optical coherence tomography angiography (OCTA) and to find out the differences in therapeutic efficacy between ischemic and nonischemic retinal vein occlusion (iRVO or non-iRVO) after conbercept treatment. Methods. In this prospective, randomized, and comparative study, 60 unilateral eyes suffered from RVO combined with macular edema were included and fellow eye as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Conbercept not only enables extensive inhibition of neovascularization and inflammatory response but also reduces damage to retinal capillary endothelial cells, effusion and retinal edema, thereby inhibiting capillary leak, resolving retinal and macular edema and improving visual acuity. 4 - 6 Results of our study also showed that conbercept could effectively improve the BCVA and CMT of patients with non-ischemic CRVO, which was similar to the results of previous studies. Studies have demonstrated that intravitreal injection of conbercept has satisfactory short-term efficacy and safety in treating secondary ME; however, the recurrence rate is relatively high and multiple injections are required, which brings a heavy financial burden and physical pain to patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conbercept not only enables extensive inhibition of neovascularization and inflammatory response but also reduces damage to retinal capillary endothelial cells, effusion and retinal edema, thereby inhibiting capillary leak, resolving retinal and macular edema and improving visual acuity. 4 - 6 Results of our study also showed that conbercept could effectively improve the BCVA and CMT of patients with non-ischemic CRVO, which was similar to the results of previous studies. Studies have demonstrated that intravitreal injection of conbercept has satisfactory short-term efficacy and safety in treating secondary ME; however, the recurrence rate is relatively high and multiple injections are required, which brings a heavy financial burden and physical pain to patients.…”
Section: Discussionsupporting
confidence: 90%
“…1 - 3 ME patients were largely administered with conbercept, a vascular endothelial growth factor (VEGF) inhibitor proven to produce desired therapeutic effect in treating neovascularization in fundus and relieve ME based on a multiple-dosing regimen. 4 - 6 …”
Section: Introductionmentioning
confidence: 99%
“…ME due to RVO (RVO-ME) is sight-threatening and unlikely to improve without treatment [4] , but can be treated by antivascular endothelial growth factor (anti-VEGF) drugs. Recent trials have shown that anti-VEGF therapies (ranibizumab, aflibercept and conbercept) can improve ME in RVO-ME patients [5][6][7] . Ranibizumab was the first and most extensively used anti-VEGF drugs [8] .…”
Section: Introductionmentioning
confidence: 99%